LV and MV polymeric insulated cables for use by distribution and generation utilities. Specification for power cables having rated voltages of 3.8/6.6 kV and 6.35/11 kV with special fire performance for use in power stations. Single core and 3-core cables with halogenated materials and with aluminium or steel wire armouring Part 7.1, (16th June 2003) - British Standards Institution,
No abstract available